Adopting YouTube to Promote Health: Analysis of State Health Departments - Duke, Carmen H (Perm J, 2019)
INTRODUCTION: We describe videos posted to the YouTube video-sharing Web site by US state health departments (SHDs) and associated institutional factors. METHODS: YouTube channels from SHDs were identified, their data retrieved, and their videos saved to a playlist on January 10, 2016. Ten randomly sampled videos from each channel were manually coded for topics. The 2012 Association of State and Territorial Health Officials profile survey was used to obtain information on staff, expenditure, and top 5 priorities for each SHD. Descriptive statistics and univariable regression were conducted. RESULTS: Forty-three SHDs had YouTube channels. Together, all SHDs posted 3957 videos, accumulated 12,151,720 views, and gained 6302 subscribers. In total, 415 videos were manually coded. Information about the agency (17.6%), communicable diseases (12.5%), and mother/infant health (8.9%) comprised the largest share of topics. No statistically significant association was observed between the log-transformed number of videos posted on an SHD’s YouTube channel and any of the explanatory variables of SHD staffing and expenditure in 2011. The number of full-time employees (r = 0.34, p = 0.03), number of epidemiologists and biostatisticians (r = 0.41, p = 0.01), and 2011 total year expenditure (r = 0.38, p = 0.02) were positively correlated with the log-transformed number of views per YouTube video posted by SHDs. No meaningful patterns of statistical association were observed between the percentage of expenditure on a specific program area and the topics of videos. CONCLUSION: Most SHDs are using YouTube, which provides a unique opportunity for SHDs to disseminate health messages.